2021
DOI: 10.3390/jcm10102065
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Pathway of Tryptophan Metabolism in Small Intestinal Bacterial Overgrowth—A Pilot Study with Patients Diagnosed with Lactulose Hydrogen Breath Test and Treated with Rifaximin

Abstract: Small intestinal bacterial overgrowth (SIBO) is a condition associated with diverse clinical conditions and there is no gold standard in its diagnosis and treatment. Tryptophan (Trp) metabolism may be involved in etiology of gastrointestinal diseases and is regulated by intestinal microbiota. In our study we investigated aspects of the serotonin (5-HT) pathway of Trp metabolism in three groups of individuals based on the hydrogen concentration in the lactulose hydrogen breath test (LHBT): controls (<20 ppm)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…We did not interfere with the diet of enrolled individuals, but we did not observe any difference between the urine concentration of TRP in the patients and the control groups and the 5 ′ -HIAA/TRP ratio was also the same in both groups. Another limitation of our study was to not measure the level of 3-hydroxykynurenine, a product of the KYN pathway of TRP metabolism, especially since this molecule is reported to exert a dual, pro-, or anti-oxidative action in the central nervous system [49]. Moreover, increased conversion of TRP to KYN with a decrease in KYNA/QA ratio suggests that the level of 3-hydroxykynurenine might change [50].…”
Section: Discussionmentioning
confidence: 97%
“…We did not interfere with the diet of enrolled individuals, but we did not observe any difference between the urine concentration of TRP in the patients and the control groups and the 5 ′ -HIAA/TRP ratio was also the same in both groups. Another limitation of our study was to not measure the level of 3-hydroxykynurenine, a product of the KYN pathway of TRP metabolism, especially since this molecule is reported to exert a dual, pro-, or anti-oxidative action in the central nervous system [49]. Moreover, increased conversion of TRP to KYN with a decrease in KYNA/QA ratio suggests that the level of 3-hydroxykynurenine might change [50].…”
Section: Discussionmentioning
confidence: 97%
“…In our previous works, we considered tryptophan metabolism in the context of the gut-brainmicrobiota axis [44][45][46][47]. However, those studies were performed on hospital patients, but this study enrolled patients of an outpatient clinic and most of them were not willing to donate blood or undergo the examination of the gut and the microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Rifaximin could inhibit bacterial overgrowth in the small intestine by modifying the intestinal microecology [18]. Therefore, rifaximin has been used to treat small intestinal bacterial overgrowth (SIBO), a heterogeneous syndrome characterized by an increased number and/or abnormal type of bacteria in the small bowel [19,20]. Jian et al [21] showed that rifaximin ameliorated non-alcoholic steatohepatitis in mice through regulating gut microbiome-related BAs.…”
Section: Introductionmentioning
confidence: 99%